Learning solutions : what to do if your child has trouble with schoolwork - Naparstek, Nathan (Emerald Publishing Limited : Information Age Publishing, 2010)
The Learning Solution is a practical guide for parents who want to improve their child's academic situation in school. It is written by a practicing school psychologist to give parents effective strategies for making the most helpful and realistic choices for children experiencing difficulty with their schoolwork.The Learning Solution will provide parents with the skills needed to negotiate the education maze and teach them how to advocate for their child. Parents will also learn how build an effective cooperative relationship with their child at home.The Learning Solution has been updated to include a chapter on mental health issues currently impacting on children's learning experiences in school. In addition, current information is provided on the medications used in the treatment of Attention Deficit Hyperactivity Disorder.
Keywords: Remedial teaching.; Education -- Parent participation.; Tutors and tutoring.; Education -- Parent Participation.; Remedial education and teaching.; elektronické knihy; electronic books